Assessment of Peppers and Soils for Some Heavy Metals from Irrigated Farmlands on the Bank of River Challawa, Northern Nigeria - Awode, U.A.; Uzairu, A.; Balarabe, M.L.; Harrisson, G.F.S.; Okunola, O.J. (Pakistan Journal of Nutrition, 2008)
Assessment of metal-contaminated soils depends on how one can predict the bioavailability of trace and toxic metals in soil and transfer to the human food chain. To predict the uptake of Cd, Zn and Ni by vegetable (pepper) grown on agricultural soil on the bank of river Challawa. 32 pepper and 16 soil samples were collected from areas irrigated with wastewater as study samples and for comparative purposes, agricultural soil samples irrigated with fresh river water, was collected as control samples. The samples were analyzed by flame atomic absorption spectrophotometer. The validation of the sample procedure was assessed by using spiking method. The level of Cd ranged from 0.94-5.27 mg kg-1 and 0.25-1.07 mg kg-1 Dry Weights (DW) for soil and pepper samples respectively. Mean concentration of Zn ranged 123.30-205.00 mg kg-1 and 10.40-35.10 mg kg-1 for samples in similar order as above while that of Ni ranged from 39.30-99.50 mg kg-1 and 2.73-6.90 mg kg-1 also in the same order of samples as mention above. The metals were examined for dependency upon some soil factor through the use of correlation analysis, pH, Organic Matter (OM), sand fractions and clay fractions correlated positively with Cd, Zn and Ni indicating that these factors greatly control the concentration of these metals in the soils. Metal transfer factors from soil to vegetable are found less significant for Cd, Zn and Ni.